(untitled) (SOMTU Journal of Business and Management Research, 2025)
This study examines the mediating role of financial attitude in the connection between financial literacy and saving behavior among university students in Nepal. It specifically analyzes the impact of familial ties, peer groups, and self-regulation on saving behavior, as well as the mediating role of financial attitude in these dynamics. Primary data were gathered from 579 students through structured questionnaires. The model was evaluated by Partial Least Squares Structural Equation Modeling (PLS-SEM) to determine measurement reliability, construct validity, and structural linkages. Findings indicate that self-control markedly affects saving behavior, whereas family and peer influences exhibit no direct impact. The financial attitude partially mediates the links between self-control and saving behavior, as well as between family influence and saving behavior. Nonetheless, no substantial mediation impact is shown between peer influence and saving behavior. These findings highlight the significance of financial attitude as a psychological conduit that amplifies the effect of financial literacy on behavior. The research enhances the behavioral finance literature and provides practical insights for developing financial literacy programs that integrate attitudinal and behavioral elements. It underscores the necessity for targeted interventions within Nepal’s educational framework to cultivate youth financial resilience and enduring saving practices.